Low Motivation in Learning Speaking - Putri, Aulia (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2016)
This study is aimed to identify the motivation of students in learning Speaking. At first, it is found out that there were 50% of the students still have low motivation in learning speaking. This research was a qualitative research that describes the condition of students in learning speaking. The writer tried to use another method which is called Cooperative Leaning to enhance students’ motivation in learning speaking. After doing it for some period of time, it showed a result that at the end of the course, students who have low motivation decrease to 20% only. By applying cooperative learning, teacher only plays a little part in speaking in one meeting. The teacher only gives a short explanation about the lesson and then guide the students to do the rest of the activities. The improvement can be seen obviously. The percentage of students who have lack of motivation in speaking decrease significantly. Only 20 % that still feel shy to speak in front of the class, but if we put them in group, they want to participate although still play small parts in their group. They enjoy and are satisfy in learning process. Moreover, they concern with the next speaking activities.Keywords: low motivation, speaking, cooperative learning.